2022
DOI: 10.1037/emo0001023
|View full text |Cite
|
Sign up to set email alerts
|

Emotional expressions as appeals to recipients.

Abstract: Emotion expressions convey information. One important kind of information, from a communicative perspective, is information about what is demanded of the recipients of the expression. Compared to the vast body of research that focuses on whether, and to what degree, emotion expressions convey information about inner states, there is surprisingly little systematic research on the information emotion expressions convey about what the expresser wants the recipient to do. The present research documents for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…In particular, when people are prompted to take the perspective of targets of prejudice, it is common to feel sadness (Vescio et al, 2003). Witnessing sadness leads to feelings of empathy, in turn sparking helping behaviors, with sadness being the main predictor of helping behaviors (Cialdini et al, 1987; Keltner & Kring, 1998; Scarantino et al, 2021). Thus, similar to anger, perceiving sadness of others can encourage one to act, and engage prosocially.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, when people are prompted to take the perspective of targets of prejudice, it is common to feel sadness (Vescio et al, 2003). Witnessing sadness leads to feelings of empathy, in turn sparking helping behaviors, with sadness being the main predictor of helping behaviors (Cialdini et al, 1987; Keltner & Kring, 1998; Scarantino et al, 2021). Thus, similar to anger, perceiving sadness of others can encourage one to act, and engage prosocially.…”
Section: Introductionmentioning
confidence: 99%
“…The authors explain this with the notion that smiles are more ambiguous in their meaning and require some indication that the smile is indeed a positive signal before they will be mimicked. Sadness expressions, by contrast, have a strong appeal for empathy [18] and hence are less ambiguous in meaning. Whether laughter will be mimicked, should therefore depend on the perceived appropriateness of the observed behaviour and the perceived closeness of expresser and observer.…”
Section: (E) the Role Of Facial Mimicry In Social Affiliationmentioning
confidence: 99%
“…A recent study, conducted in the context of the Korean conflict, revealed that the effect of South Koreans' group based hatred on support of military action against North Korea as well as on support for conciliatory policies, went above and beyond various variables, such as ideology and group identification, (Halperin and Nir 2019). Emotions can be explained as mental states of readiness (Scarantino and de Sousa 2018), incorporating motivation and directed action towards a certain target (Bagozzi et al 1999). As such, their role as mediating factors between social reactions to COVID-19 and intergroup escalation and cooperation may be especially important.…”
Section: Group Based Emotions In Intergroup Conflictmentioning
confidence: 99%